KOMODIFIKASI AGAMA, GENDER, DAN ANAK DI MEDIA DIGITAL: NEGOSIASI KESALEHAN, IDENTITAS, DAN ETIKA PERLINDUNGAN SUBJEK RENTAN - Asmarandani Heryadi Putri; Doddy S. Truna; Roro Sri Rejeki Waluyajati (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2025)
The phenomenon of the commodification of religion in digital media signifies a fundamental shift in the ways spiritual values are produced, represented, and consumed in contemporary society. Digital media no longer function merely as channels for religious communication, but also as arenas of symbolic economy governed by algorithmic logic and platform capitalism. In this context, religion tends to shift from a transcendental experience toward a visual performance measured by popularity, attention, and exchange value. This study aims to analyze the commodification of religion in digital media by emphasizing the perspectives of gender and children as socially vulnerable subjects. Employing a critical-interpretative qualitative approach, the research draws on literature review, qualitative observation of digital religious content, and thematic-critical analysis grounded in the philosophy of communication, critical theory, and ethical studies. The findings indicate that representations of women and children in digital religious content often function as visually effective symbols of piety, yet they are prone to symbolic reduction and objectification. Furthermore, the study reveals that algorithmic logic encourages the simplification of religious messages and reinforces religious performativity, thereby marginalizing the reflective and ethical dimensions of faith. Nevertheless, digital media also provide new opportunities for more inclusive religious participation and expression, provided that such practices are accompanied by critical awareness and moral responsibility. This study underscores the urgency of developing an ethical framework for digital religious communication that prioritizes human dignity, particularly that of women and children, amid the dynamics of digital capitalism.